Optimisation of narrowband optical filters for 10 Gbit/s directly modulated laser transmitters - Śliwczyński, Łukasz; Krehlik, Przemysław; Buczek, Łukasz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Filtering of the chirped signal from a directly modulated laser with the narrowband optical filter with a high roll-off allows to in-crease the dispersion tolerance of the transmitter substantially. In the paper, the influence of the parameters of the filter on the performance of the fibre link is analysed. Investigations are carried out for both band-pass and band-stop filters. Basing on the numerical modelling of the fibre link, the parameters of the filter are searched that give the smallest dispersion penalty. Theoretical investigations are supported by hardware experiments confirming correctness of applied methods and models.
Optica Applicata, Vol. 40, 2010, nr 1, s. 33-47
Keywords: optyka; directly modulated laser; optical filtering; dispersion tolerance; dispersion penalty